UPAYA MENINGKATKAN KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR SISWA DENGAN MODEL PROBLEM BASED LEARNING PADA MATERI GELOMBANG DI KELAS XI F1 SMAN 4 KOTA JAMBIUPAYA MENINGKATKAN KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR SISWA DENGAN MODEL PROBLEM BASED LEARNING PADA MATERI GELOMBANG DI KELAS XI F1 SMAN 4 KOTA JAMBI - Erlita Gultom; Darmaji Darmaji; Jeliana Veronika Sirait (STKIP Pesisir Selatan, 2026)
This study aimed to improve students' science process skills and learning outcomes through the implementation of the Problem-Based Learning (PBL) model on the topic of waves in Grade XI at SMA Negeri 4 Jambi City. This research employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, which consists of four stages: planning, action, observation, and reflection. The study was conducted in three cycles involving 36 students of class XI F1, comprising 11 male students and 25 female students. Data were collected using observation sheets to assess students' science process skills and multiple-choice tests to measure learning outcomes in each cycle. The data were analyzed quantitatively using descriptive statistics based on the percentage of achievement of science process skill indicators and learning mastery. The results showed that the implementation of the PBL model improved students' science process skills from 66.5% in Cycle I to 71.6% in Cycle II and further increased to 80.2% in Cycle III. In addition, students' learning mastery improved from 75% in Cycle I to 89% in Cycle II and reached 92% in Cycle III. Therefore, the Problem-Based Learning model was effective in improving students' science process skills and learning outcomes on the topic of waves.